Quality of Life of COVID-19 Pfizer® Booster Vaccine Recipients Using Short Form-8 Instrument in Palu City - Arya Dibyo Adisaputra; Amelia Rumi; Khusnul Diana; Salza Syahdianti Rahmadani (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
The COVID-19 pandemic continues, and vaccination initiatives are still underway. Booster vaccinations are administered to enhance antibodies that decline after several months of receiving the primary vaccine doses. It is important to understand the impact of these vaccinations on recipients' quality of life. This study aims to examine the influence of demographic and clinical characteristics on the quality of life of the population in Palu City who received the Pfizer® COVID-19 booster vaccine. This research is an observational, cross-sectional study. The sampling was conducted using the consecutive sampling method, and a total of 400 individuals who met the inclusion criteria were included as the sample. This study used the Short Form-8 questionnaire to assess quality of life. Data analysis was performed using multiple linear regression. The study found that the quality of life of individuals who received the Pfizer® COVID-19 booster vaccine in Palu City was good, as evidenced by average domain scores≥50. An individual's quality of life can be assessed in terms of physical and mental aspects. Post-vaccination symptoms and a history of COVID-19 infection (p<0.05) influenced the physical aspect. Age, occupation, and a history of COVID-19 infection (p<0.05) influenced the mental aspect. The quality of life of the population in Palu City who received the Pfizer® COVID-19 booster vaccine showed a greater improvement in mental health than in physical health.